PENGARUH MEDIA PEMBELAJARAN BERBASIS GAMIFIKASI TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SDN 117505 PANJANG TONGAH - Ummi Nadhrah; Natalia Silalahi; Khairul Usman (STKIP Subang, 2026)
This study aims to determine the effect of gamification-based learning media through the Padlet application on Indonesian language learning outcomes in the material